A new species of Croton section Cleodora (Euphorbiaceae s.s.) from Minas Gerais, Brazil - Caruzo, Maria Beatriz Rossi; Cordeiro, Inês; Berry, Paul E.; Riina, Ricarda (Phytotaxa, 2013)
Croton stellatoferrugineus, a new species from Brazil, is here described and illustrated. This new species is endemic to dry forests at the base of “Pico do Itambé”, the highest point of the Espinhaço range, in Minas Gerais State, occurring at 700–900 m elevation. Croton stellatoferrugineus presents morphological features consistent with its inclusion in Croton section Cleodora, due to its shrubby habit, petiolar basilaminar glands, 15 stamens, pistillate flowers with quincuncial aestivation, and multifid styles connate at the base.